Studying Quantum-state Resolved Molecule Surface Collisions - ALEXANDER BURDEN (2023)
The interaction between molecular hydrogen and a surface is of vital importance to many areas of scientific research. Thus, understanding this interaction and being able to model it is very beneficial. The goal of this master’s thesis is to characterise the interaction of hydrogen scattering from a hydrogen passivated chromium(110) surface. The thesis will describe the surface scattering measurements as well as the techniques previously developed to allow for these measurements. The quantum mechanical state of the molecular hydrogen is coherently controlled both before and after the scattering with the surface to theoretically allow for extraction of the scattering matrix from this data, which completely describes the interaction. Scattering both under specular and diffraction channel conditions were described, with the scattering at specular conditions demonstrating that the surface appears as a mirror to the hydrogen under these conditions. However, due to the noise encountered when measuring the signal when scattered into the (0,1) diffraction channel, the results for the scattering matrix for this this measurement are not entirely conclusive. This thesis will demonstrate that the measured signals are still able to provide a benchmark for theoreticians modelling the interaction. We then explore the various possible results for the scattering matrix and the conclusions we can draw from these, such as the high probability that hydrogen molecules rotating as helicopters relative to the surface ( = ±1) are more likely to scatter into the (0,1) diffraction channel than those rotating as cartwheels ( = 0). A possible resolution to these variety of results is just examining the best fit result to the experimental data; this thesis will describe this result and also explore the extent to which this result can be regarded over other possible solutions. Finally various data treatment options such as frequency filtering will be investigated in attempt to clarify the results from our experimental data.